Immigration detention, punishment and the transformation of justice - Bosworth, M (SAGE Publications, 2017)
In this article, I examine the changing nature of punishment under conditions of mass mobility. Drawing on research conducted in immigration removal centres in the UK, I will show how porous boundaries between administrative penalties and criminal penalties have made the two systems co-constitutive and, in so doing, have drawn into question the liberal foundations of punishment. As foreigners face additional, administrative burdens and are subject to processes of differentiation and exclusion simply by virtue of their citizenship, I suggest, basic values of due process, fairness and equality of treatment and outcome, are drawn into question. As a consequence, justice itself is transformed.